Towards developing comprehensive business intelligence maturity model for Malaysian Public sector: application of mixed methodology - Zahrullaili, Muhammad Harith; Noordin, Muhammad Fauzan (IEEE, 2018)
This paper is a part of an ongoing study on developing an extensive business intelligence (BI) maturity model for government agencies in Malaysia. In our endeavor to achieve this objective, we highlight the need of new BI maturity model to provide a holistic understanding towards BI maturity as existing models are generic, incomprehensive, and lack of tools to support its practical usage. To address this issue, we proposed a new structure of maturity model and an unconventional mixed- methodological framework to construct the respective model.